2015
DOI: 10.1093/mnras/stv1215
|View full text |Cite
|
Sign up to set email alerts
|

LMC S63: a historical reappraisal of the outburst behaviour of a deeply eclipsing Magellanic symbiotic star

Abstract: We present an analysis of multi-epoch low-resolution spectrophotometry, complemented by the light curves provided by massive photometric surveys spanning over 100 years, of the symbiotic binary LMC S63. We showed that it is an eclipsing binary with the orbital period of 1050 d . We also found evidence of outbursts in history of the white dwarf. If it was a Z-And type outburst, as is most likely, it would be a second such outburst recorded in the Magellanic Cloud symbiotic system. We confirmed that the red gian… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…A good example is symbiotic S63 in LMC where C/O ratio seems to grow continuously ( Fig. 14) after active phases (Iłkiewicz et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A good example is symbiotic S63 in LMC where C/O ratio seems to grow continuously ( Fig. 14) after active phases (Iłkiewicz et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in some SySt the He i emission line ratios are correlated with the orbital phase (e.g. Iłkiewicz et al 2015), so some SySt can possibly be found in the region occupied by PNe only at certain orbital phase. Furthermore, in some SySt He i lines can be observed only during active phases (e.g.…”
Section: Distinguishing Between Syst and Pnementioning
confidence: 99%
“…Moreover, in the case of a SySt with a C-rich giant, a weak He ii 4686 line can be also easily buried in the C 2 4737 band. This effect is clearly visible in the spectra of the known SySt LMC S63 taken near the hot component eclipse (Iłkiewicz et al 2015). We maintain, however, that this is a price that the SySt community must be willing to pay to prevent wholesale contamination of extragalactic SySt catalogs with imposters that have nothing to do with SySt.…”
Section: M33sys Jmentioning
confidence: 93%
“…However, the colour changes are larger for larger amplitudes and longer pulsation periods (Mira or LPV variables), and often negligible in low-amplitude semiregular (SR) variables. The orbital variability can be detected only in S-type SySt where the red giant is nonvariable or an SR variable (Gromadzki et al 2013;Iłkiewicz et al 2015). In these SySt, the orbital modulation is best visible in the visual and blue bands while the low amplitude SR pulsations in these SySt dominate in the red bands (in SySt with strong emission lines the SR pulsations are visible only during the orbital minimum).…”
Section: M33sys Jmentioning
confidence: 98%